The relationship between the manuscripts of the Aṭṭhakesadhātu - Udomsinprasert, Kasidis; Vithidkul, Jiaranai (Journal of Buddhist Studies Chulalongkorn University, 2025)
The Aṭṭhakesadhātu, the once-known story of the installation of 8 strands of the Buddha’s hair relics, has been copied and passed down in several languages and scripts used in Thailand. Despite being surveyed and mentioned in some catalogues, this literature has never been studied even in the simplest aspect. This research, therefore, focusing on all 12 survived witnesses of Aṭṭhakesadhātu in Pali language with Khom script, aims to study the relationship between each manuscript in order to investigate the recensions of the text. The text in each manuscript is carefully compared word by word to examine the similarities and differences which can be used for indicating the connection between each manuscript and creating the stemmas of the text. The study finds that, according to the existing manuscripts, two stemmas of the Pali Aṭṭhakesadhātu texts can be assumed. The first stemma has two parallel main branches with many sub-branches underneath each of them. In contrast, the second one can be depicted as a tall tree which gradually grows and changes, with no major branch sharply divided.